Penanganan Keluhan Tamu dengan Metode ILEAD Oleh Karyawan Kantor Depan di Hotel Holiday Inn Resort Baruna Bali - I Kadek Ngurah Sukamerta; Nyoman Dini Andiani (Universitas Pendidikan Ganesha, 2020)
The strategy for handling guest complaints is very important to be improved because it is able to create quality service and a good cooperative relationship with guests. This research is a qualitative research with descriptive analysis. The purpose of this study was to determine the Complaints Handling Strategy conducted by Front Office employees at the Holiday Inn Resort Baruna Bali Hotel. The data obtained are primary data obtained from interviews with Front Office Managers. The results showed that the Complaints Handling conducted by front office employees at the Baruna Bali Holiday Inn Resort used the ILEAD method, namely Identify, Listen, Empathize, Apologize, and Deliver Solution. The ILEAD method as a complaint handling strategy has been running well.